Impresionalisasi Kepemimpinan Kepala Sekolah terhadap Mutu Layanan - M Zen Syukri; Bukman Lian; Nila Kesumawati (Journal Of Administration and Educational Management (ALIGNMENT), 2023)
This study aims to describe the influence of the principal’s leadership toward the quality of service at SMA Subrayon 01 Palembang. This research used quantitative descriptive approach with 62 respondents and got data by using questionnaire, observation, and documentation, the data gotten were tested by using prerequisite test and analyzed by using linear regression analysis. The result of the study showed that the principal’s leadership influnced highly toward the quality of service at SMA Subrayon 01 Palembang. In conclusion, the principal has a high level of commitment to the quality of service at SMA Subrayon 01 Palembang Keywords: the principal’s leadership; the quality of service